Epidemiological characterization of malaria transmission in indigenous communities in the department of Amazonas. 2009-2019 - Bustamante-Chauca, Tomás Pershing (2020)
Objetive: Describe the main epidemiological characteristics of malaria transmission in indigenous communities in the department of Amazonas, 2009 - 2019 ( SE. 21) and recurrence by type of plasmodium in the same period. Material and Methodo: Observational, descriptive, cross-sectional retrospective study of malaria cases reported in the department of Amazonas from 2009 to SE 21 of 2019. 3,191 records of cases reported with malaria were included. For the data processing, the bases were loaded in an electronic spreadsheet of Microsoft Office Excel 2013. For the analysis, Excel and the STATA 14 statistical program were used. The data is expressed in descriptive statistics (measure of central tendency and dispersion), frequency tables, proportions and incidence rates. Results: In the study population it was found that 95.82% were infected by P. vivax; the median age was 11 years with a range between 19 days and 82 years; 52.75% were male and 69.24% of the cases are under 19 years old; As of 2019, there is an increase in cases of P. Falciparum. In the last 10 years a recurrence of 2 to 6 times was found for each infected person. The most affected population corresponds to the province of Condorcanqui. Conclusions: In the last 10 years, the diagnosis of P. Vivax malaria predominates, the most vulnerable group being those under 19; There is also a high percentage of reinfections and / or relapses for plasmodium vivax malaria (95%).